LAW VIOLATION EFFECTS OF CODES CONDUCTED BY NOTARY - Ngadino Ngadino (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2019)
This study aims to determine the legal consequences in case of violations of the code of conduct by notary and notary determine responsibility in the event of violation of professional ethics. The method used is empirical juridical approach. The method used is a qualitative method. Specifications research in writing this research is a descriptive analytical research. Methods of data collection for primary data obtained through interviews guided free.Based on research conducted can be concluded that 1) Due law violation in case of code violations by the notary is a Notary Public who breach the code of conduct as defined in the legislation then the solution is based on provisions itself, so that the legal certainty of the notarial profession is guaranteed. Notary who commits an offense against ethics, decency or moral solution not only according to the code of ethics alone, but can also be based on legislation. Everything that is not done by the notary clearly and expressly set forth in the form of legislation; 2) The notary public responsibilities in the codes violation is when notary did violation to the code of Indonesian Notary Association (INI) or another people who has notary position in the duties or daily activity.Keywords: Due To The Legal; Ethical Codes Notaries; Notary.